Effects of Mycorrhiza Doses and Manure Types on Growth and Yield of Cassava in Gunungkidul - Astuti, Agung; Mulyono, Mulyono; Hariyono, Hariyono; Meitasari, Retno (PLANTA TROPIKA, 2022)
Gunungkidul is a production center of cassava (Manihot esculenta Crantz), a carbohydrate source and raw material for food industry. AMF inoculation in cassava plants is known to increase biomass production. However, little studies have been conducted on the response of cassava to mycorrhizal inoculation and organic fertilizer. Therefore, this study was aimed at examining the effects of AMF inoculation and types of manure on the AMF colonization and yield of cassava in Gunungkidul. The research was carried out by planting cassava in Alfisol Gunungkidul arranged in a randomized complete block design with two factors, AMF doses of 25g; 50; and 75g/plant; and types of manure i.e. cow, goat, and poultry manure, for five months period. Rhizosphere soil and root samples were analyzed for AMF colonization and the spores number. The results showed that AMF-infected cassava roots combined with cow or goat manure application produced more spores than poultry manure. AMF infection and manure, thus, significantly resulted in better root proliferation, root forehead weight, tuber diameter, and cassava products, than the absence of both treatments. Cow manure combined with AMF at a dose of 25 g/plant significantly affected the dry weight of cassava roots. This study implies that applying AMF and manure provide a substantial contribution on the growth and production of cassava.